DETEKSI SERANGGA HAMA PADA GUDANG PENYIMPANAN BIJI PINANG (Areca catechu) MENGGUNAKAN BEBERAPA METODEPENGAMBILAN SAMPEL - Santi Sandra; Lizawati Lizawati; Wilyus Wilyus (Jurnal Media Pertanian, 2021)
The research aims to detect insect in betel nut storage (Areca catechu) using some sampling methods. The research was conducted by survey method using three sampling methods, namely hand sampling method, yellow sticky trap method, and dome trap method. The parameters observed were types of insect pests found, insect populations obtained, and abundance of pest insect populations. The research was conducted from July to October 2018 in four betel nut storagesin Jambi City and Muaro Jambi District. Insects found in the betel nut storages with three sampling methods were 28 pest species. In the hand sampling method found 16 types of pest insects, in the yellow sticky trap trap method found 21 types of insect pests, and in the dome trap method found 21 types of insect pests. The dominant insects found in the three sampling methods were Ahasverus advena, Araecerus fasciculatus, Callosobruchus spp., Carpophilus dimidiatus, Cryptolestes ferrugineus, Cryptolestes pusillus, Hypothenemus hampei, Lasioderma serricorne, Lophocateres pusillus, Oryzaephilus mercator, Typhaea stercorea, and Tribolium castaneum.